Systematic radical species control by electron push–pull substitution in the perylene-based D–π–A compounds. Issue 4 (13th January 2023) - Ahn, Mina; Lee, Soyoon; Kim, Min-Ji; Chae, Minjung; Cho, Dae Won; Wee, Kyung-Ryang
Abstract : (D–π–A)˙ − & (D–π–A)˙ + are generated in response to electrical stimulation. Unlike (D–π–A)˙ −, (D–π–A)˙ + shows a systematically controllable substituent effect by the DPA R group ranging from electron-withdrawing F to electron-donating OMe group. Abstract : Organic radical materials have been mainly reported on the stabilization of radical species because of their high energy and reactivity, while design strategies for controlling radical species beyond stabilization have remained challenging. Here, we report the electronic push–pull control spanning the neutral to the radical state of a series of perylene-based donor–π–acceptors (D–π–A). By introducing electron-withdrawing and -donating R groups to the donor of D–π–A, the observed intramolecular interactions controllable at the HOMO level led to the exploration of radical species. D–π–A with redox-active sites was transformed to (D–π–A)˙ + and (D–π–A)˙ − in response to an external electrical stimulus under stabilization by perylene, resulting in new absorption peaks. In particular, the increasing absorption peaks of (D–π–A)˙ + showed a spectral shift and intensity change according to the R group, unlike those of (D–π–A)˙ − . These experimental results support that the DFT/TD-DFT data suggests the radical cationic SOMO level variability. As a result, we provide a strategy for controlling the systematic radical species using the electron push–pull effect.